Conserved localization of Pax6 and Pax7 transcripts in the brain of representatives of sarcopterygian vertebrates during development supports homologous brain regionalization - Nerea eMoreno; Ruth eMorona; Alberto eJoven; Sandra eBandín; Jesús M López; Agustín eGonzález (Frontiers Media S.A., 2014)
Many of the genes involved in brain patterning during development are highly conserved in vertebrates and similarities in their expression patterns help to recognize homologous cell types or brain regions. Among these genes, Pax6 and Pax7 are expressed in regionally restricted patterns in the brain and are essential for its development. In the present immunohistochemical study we analyzed the distribution of Pax6 and Pax7 cells in the brain of six representative species of tetrapods and lungfishes, the closest living relatives of tetrapods, at several developmental stages. The distribution patterns of these transcription factors were largely comparable across species. In all species only Pax6 was expressed in the telencephalon, including the olfactory bulbs, septum, striatum and amygdaloid complex. In the diencephalon, Pax6 and Pax7 were distinct in the alar and basal parts, mainly in prosomeres 1 and 3. Pax7 specifically labeled cells in the optic tectum (superior colliculus) and Pax6, but not Pax7, cells were found in the tegmentum. Pax6 was found in most granule cells of the cerebellum and Pax7 labeling was detected in cells of the ventricular zone of the rostral alar plate and in migrated cells in the basal plate, including the griseum centrale and the interpeduncular nucleus. Caudally, Pax6 cells formed a column, whereas the ventricular zone of the alar plate expressed Pax7. Since the observed Pax6 and Pax7 expression patterns are largely conserved they can be used to identify subdivisions in the brain across vertebrates that are not clearly discernible with classical techniques.